Keanekaragaman Kupu-Kupu (Rhopalocera) di Sumber Mangli dan Sumber Clangap Desa Puncu Kecamatan Puncu Kabupaten Kediri - Nanda Anggyka Wulandary (UIN Sunan Gunung Djati Bandung, 2021)
Butterflies are a type of insect with the main characteristics of the wings being covered with scales. Butterflies can be found in almost all habitats, especially on river banks. Sumber Mangli and Sumber Clangap are springs located in Puncu Village, Puncu District, Kediri Regency. The ecosystem around the two springs is still very well maintained. The diversity of butterflies in the two springs areas is still lacking in information and not much research has been done. This research was conducted to know the diversity of butterflies in Sumber Mangli and Sumber Clangap. This study uses visual day flying and transect belt methods to obtain data on the number and types of butterflies. The data were analyzed using the Shannon-Wiener Diversity Index. The results of this study indicate that in Sumber Clangap found 28 species from 6 families, while in Sumber Mangli found 10 species from 5 families. The results of the analysis show that the species diversity index in the Sumber Clangap is higher at H'= 2.61, compared to the Sumber Mangli, which is H'= 2.16.